Valuation of gender role participation in coastal resource management in Masinloc, Zambales, Philippines - Sumalde, Zenaida M.; Dayo, Maria Helen F. (2015)
Recognizing the importance of incorporating gender dimension into any development and conservation programs, gender analysis has become an important input in decision making that gives particular attention to sustainability of the programs. Using the case of Masinloc, Zambales, this study identifies the roles of men and women in the coastal resource management (CRM) and estimates the value of time spent by men and women in CRM activities. Gender-segregated data were gathered from 50 households where husband and wife from each household were separately and simultaneously interviewed using the same set of questionnaire, thus making a total of 100 respondents. Results of the analysis show that incorporating gender dimension into CRM research study affects the outcomes. Logit analysis shows that gender, awareness of the CRM activities and membership in organization significantly affect the decision to participate in CRM activities. On the other hand, the Tobit regression analysis shows that gender, household income, awareness about the CRM and membership in an organization affect the time devoted to and value of time spent in CRM activities. From the results, recommendations on how to incorporate gender dimension in CRM activities are forwarded.
Keywords: Gender mainstreaming; Coastal zone management -- Masinloc (Zambales)